2016
DOI: 10.18632/oncotarget.7539
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor nuclear translocator (ARNT) isoforms control lymphoid cancer cell proliferation through differentially regulating tumor suppressor p53 activity

Abstract: The aryl hydrocarbon receptor nuclear translocator (ARNT) is involved in xenobiotic and hypoxic responses, and we previously showed that ARNT also regulates nuclear factor-κB (NF-κB) signaling by altering the DNA binding activity of the RelB subunit. However, our initial study of ARNT-mediated RelB modulation was based on simultaneous suppression of the two ARNT isoforms, isoform 1 and 3, and precluded the examination of their individual functions. We find here that while normal lymphocytes harbor equal levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
2
23
0
1
Order By: Relevance
“…This mechanism supports recent findings showing that promotion of certain blood cancers (e.g. human multiple myeloma and anaplastic large cell lymphoma) rely on ARNT by antagonizing RelB and p53-dependent cell-cycle arrest and apoptosis (121). Expression of RelB was also shown to be critical for survival of Hodgkin lymphoma (122).…”
Section: Resultssupporting
confidence: 91%
“…This mechanism supports recent findings showing that promotion of certain blood cancers (e.g. human multiple myeloma and anaplastic large cell lymphoma) rely on ARNT by antagonizing RelB and p53-dependent cell-cycle arrest and apoptosis (121). Expression of RelB was also shown to be critical for survival of Hodgkin lymphoma (122).…”
Section: Resultssupporting
confidence: 91%
“…For instance, the IRES activity of TNF receptor-associated factor 1 (TRAF1) is simulated in leukemic cells treated with vincristine, the 5'-UTR of human sensitivity to nitrogen mustard (hSNM1) upregulates protein expression in HT-1080 cells during mitosis, and several apoptosis-inducing agents induce the IRES activity of cellular inhibitor of apoptosis protein 1 (c-IAP1) in 293T cells (42)(43)(44). Furthermore, previous studies have demonstrated that AHR nuclear translocator (ARNT isoform 1) impairs chemo-resistance and survival to cancer cells (45). Thus, the increasing concentration of chemotherapeutic drug PTX was used to treat A2780, MB231, Bel7402 and SW620 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of arnt , cdh2 , foxc2 , polb , and the overexpression of e2f4 and pinx, can help to explain the expressive pro-apoptotic effects exhibited by N9 in our study. Indeed, these genes are able to modulate the survival rates of various tumor cell lines 36 40 . Most of them have also been involved in cell migration, invasiveness, metastasis and angiogenesis 37 , 39 , 41 , and their regulation likely contributes with the tumor control.…”
Section: Resultsmentioning
confidence: 99%
“…The compounds N15 (R = 3′,4′,5′-triOCH 3 ), N16 (R = 3′-OCH 3 , 4′-OH), N17 (R = 2′,4′,5′-triOCH 3 ), N18 (R = 3′,5′-diOCH 3 ), N19 (R = 2-OCH 3 ), N20 (R = 3′,5′-diOCH 3 , 4′-OH), N23 (R = 3′-OCH 3 ) and N36 (R = 2′,3′,4′-triOCH 3 ) were described by Winter et al . (2014) 36 . The compounds N24 (R = 4-imidazol), N33 (R = 4-CN), N34 (R = 3-CN) and N37 (R = 4-F) are new chalcones.…”
Section: Methodsmentioning
confidence: 99%